Investigating The Effects Of Solid Waste Dumps On Surrounding Soil And Ground Water Quality Around Umuwaya Road (Isi-Gate) Umuahia, Abia State - Onyekwere Precious; Chioma Nwakanma (Tecno Scientifica Publishing, 2022)
An increase in industrialization, urbanization, and the rising demand for food and other essentials for human sustainability leads to a rise in the amount of waste being generated daily by individuals, communities, and nations if not properly managed. In Abia State, particularly at the central entrance into the city of Umuahia, generated waste is eventually thrown into open dumps, causing a severe impact on soil, surface and ground water quality. As a result, it has become a probable source of human health risk. Therefore, this study was aimed at investigating the effect of solid waste dumps on surrounding soil and groundwater quality in Umuwaya Road, Nigeria. Three soil samples and three groundwater samples were collected and analyzed. Heavy metals from soil and groundwater were measured by using flame atomic absorption spectroscopy. The physicochemical properties of the soil and water samples were also determined following standards. The data was analyzed using the descriptive SPSS statistical package. The concentration of heavy metals in soil samples revealed copper (0.01±0.00–0.26±0.07), cadmium (0.00±0.00–0.18±0.01), lead (0.03±0.01–0.40±0.03), iron (0.06±0.01–0.58± 0.02) and zinc (0.02±0.01–0.20± 0.04). All the water parameters and heavy metals screened in the samples were within the World Health Organization (WHO) and Nigeria Standard for Drinking Water Quality (NSDWQ) permissible limits, respectively. It is recommended that indiscriminate waste disposal should be prohibited completely in the capital city. Waste reduction, recycling, and reuse must be promoted by the citizens of the state for a sustainable future.